Effects of methylenetetrahydrofolate reductase single-nucleotide polymorphisms on breast, cervical, ovarian, and endometrial cancer susceptibilities - Zheng Wang (KeAi Communications Co., Ltd., 2021)
Background: Recent studies identifying methylenetetrahydrofolate reductase (MTHFR) polymorphisms associated with breast cancer (BC), ovarian cancer (OC), cervical cancer, and endometrial cancer (EC) have reported conflicting results and been underpowered. To clarify the correlation between MTHFR mutations and these common female malignancies, we conducted a comprehensive meta-analysis incorporating all eligible publications. Methods: Relevant reports published before January 20, 2020, were retrieved from PubMed, Embase, the Cochrane Library, and the China National Knowledge Infrastructure databases. The odds ratio and 95% confidence interval summaries for the MTHFR 677C/T and 1298A/C polymorphisms in BC, OC, cervical cancer, and EC were estimated. Results: A total of 171 studies comprising 56,675 cancer cases and 67,559 controls were included. The results showed a markedly elevated risk of cancer susceptibility related to MTHFR 677C/T based on all genetic models. Similarly, we identified a significant correlation between 1298A/C mutation and cancer risk based on overall comparisons among all models, except the heterozygous model. Moreover, subgroup analysis by cancer type revealed a significantly increased risk of BC associated with 677C/T in the five models and of cervical cancer associated with 1298A/C in some models. Based on ethnicity, significant associations were observed between Asian, African, and mixed populations for 677C/T and the Asian population for 1298A/C. With regard to the sample type used for analysis, we detected a positive association between using blood as the DNA source and cancer risk for 677C/T in all genetic models and for 1298A/C in some genetic models. Further stratification of the results revealed that a notably increased risk was associated with the use of polymerase chain reaction-restriction fragment-length polymorphism or TaqMan as the genotyping method, as well as with the use of population-or hospital-based groups as the controls for 677C/T and 1298A/C, respectively. Conclusion: This meta-analysis suggests that MTHFR 677C/T and 1298A/C polymorphisms correlate with the risk of common gynecological cancers, with these findings potentially applicable for overall comparisons of related data.